Pendampingan: Gereja Kristen Indonesia Tegalrejo dalam Menghadapi New Normal - Putri Hergianasari; Elisabeth Priscila Tamtalahitu; Aveliani Mega Elfrieda Sinaga; End Tresya Twanggin (Universitas Kristen Satya Wacana Salatiga, 2020)
The importance of this community activity is carried out to provide assistance to the Tegalrejo Indonesian Christian Church in facing the New Normal. The objectives, firstly to provide assistance to the church, second to socialize to the Indonesian Christian Church Tegalrejo congregation, especially Sunday School children applying Clean and Healthy Behavior in facing the New Normal. The method used is the making of a Clean and Healthy Behavior videos with church administrators, socialization to Sunday school children. The result of this community service is a Clean and Healthy Behavior video for Sunday School children, an increase in the capacity of church administrators in arranging procedures for conducting worship, increasing the capacity of Sunday school children in implementing Clean and Healthy Behavior in the New Normal era. ABSTRAK Pentingnya kegiatan masyarakat ini dilakukan untuk memberikan pendampingan kepada Gereja Kristen Indonesia Tegalrejo dalam menghadapi New Normal. Tujuan, pertama memberikan pendampingan kepada gereja, kedua mensosialisasikan kepada jemaat GKI Tegalrejo terutama anak-anak Sekolah Minggu penerapan Perilaku Hidup Bersih dan Sehat (PHBS) menghadapi New Normal. Metode yang digunakan adalah pembuatan video PHBS dengan pengurus Gereja, sosialisasi pada anak-anak Sekolah Minggu. Hasil dari pengabdian masyarakat ini adalah video PHBS untuk anak Sekolah Minggu, Peningkatan kapasitas pengurus gereja dalam menyusun tata cara pelaksanaan ibadah, peningkatan kapasitas anak-anak sekolah minggu dalam melaksanakan PHBS di era New Normal.